2018
DOI: 10.1111/jcal.12300
|View full text |Cite
|
Sign up to set email alerts
|

Learning performance and cognitive load in mobile learning: Impact of interaction complexity

Abstract: In the increasing pervasiveness of today's digital society, mobile devices are changing the face of education. Students can interact with mobile devices in context-aware environment. This paper presents a mobile application based on expert system (Plant-E) for students to acquire knowledge about plant classification by answering decision-making questions. In order to study effectiveness of Plant-E and cognitive load of students who experience different kinds of interaction in learning process, another mobile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In this study, students obtained better learning achievement and higher cognitive load when they learned based on AR environments and traditional instructional model. Wang, et al [41] stated that the higher the interaction complexity is, the higher the mental effort and the better the learning performance in mobile learning will be. Since AR environments combine objects in real world and virtual world, students have more opportunities to interact with more factors during learning activity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, students obtained better learning achievement and higher cognitive load when they learned based on AR environments and traditional instructional model. Wang, et al [41] stated that the higher the interaction complexity is, the higher the mental effort and the better the learning performance in mobile learning will be. Since AR environments combine objects in real world and virtual world, students have more opportunities to interact with more factors during learning activity.…”
Section: Discussionmentioning
confidence: 99%
“…The Cognitive Load Questionnaire was developed by Hwang et al (2013) based on the measures proposed by Paas et al (1994) and Sweller et al (1998). A Chinese version of the Cognitive Load Questionnaire been used in Chinese middle school classrooms (Wang et al, 2018). The Cognitive Load Questionnaire consists of five items for mental load and three items for mental effort.…”
Section: Cognitive Load Questionnairementioning
confidence: 99%
“…This explanation of cognitive load best fits the definition of the micro level (Vavoula et al, 2009). In a mobile context, users may be required to perform additional tasks (e.g., walking), and this could have an impact on the completion of the primary task (Harrison et al, 2013; Wang, Fang, & Miao, 2018). In this review, only one study [S25] paid attention to this evaluation aspect and indicated that using mobile technology while addressing an inquiry problem in an outdoor environment was challenging for secondary school students due to cognitive overload.…”
Section: Resultsmentioning
confidence: 99%